Rising powers and the provision of transnational public goods: conceptual considerations and features of South Africa as a case study - Stephan Klingebiel (Deutsches Institut für Entwicklungspolitik (DIE), 2017)
The paper delineates three debates, which will be conflated: One line of discussion relates to public goods at transnational level. Here, the referencing of debates regarding the characteristics of “a common good” will be of significance. A second strand addresses the group of countries known as the `rising powers' and the role these countries could play as regards a globalised common good. A third discussion thread analyses South Africa as a case study for the main rising power on the African continent. By creating connections between the lines of discussion, this paper drive forward the debates on how the role of rising powers can be conceptually repositioned in the light of a changing global context, and to explore how these countries can respond to global challenges.
Keywords: 330; Regionale + globale + transnationale Governance; Rising powers